Effects of professionalism on employee satisfaction and organizational commitment at five star hotels in Baku - Guliyev, Gabil; Avci, Turgay; Ozturen, Ali; Safaeimanesh, Farzad (Nomos Verlagsgesellschaft Mbh & Co Kg, 2019)
Professionalism is one of the necessities for service operations in order to be sustainable at the current competitive markets. The purpose of the study is to evaluate the effect of attitudinal professionalism on employees' job satisfaction and organizational commitment at five-star hotels in Baku, Azerbaijan. The researchers administered questionnaires to 503 employees in the selected 30 five star hotels. Professionalism is found as a significant factor in bringing job satisfaction and commitment. The employees held strong views that their job sufficiently suits their abilities. This is a clear indication that professionalism supports their level of satisfaction with their present job. The study also revealed that the self-management dimension of professionalism has the highest effect on job satisfaction and organizational commitment of the employees. In the tourism and hospitality industry, professionalism is needed for employees to sustain self-discipline and achieve success in their objectives. The management of the hotels should ensure professionalism among employees to be able to get the desired success. By providing their human resources with the deserved value, job satisfaction and commitment can be enhanced.
Keywords: Professionalism; Job satisfaction; Organizational commitment; Human behaviour at work; Baku